Insights into biological indices of six indigenous fish species from Bihar, India - Surendra Kumar Ahirwal; Sarma, Kamal; Kumar, Tarkeshwar; Bharti, Vivekanand; Kumar, Rakesh; Singh, Jaspreet; Raut, Shailendra (Indian Journal of Fisheries, 2025)
In this study, we examined the length-weight relationship, relative condition factor and hepatosomatic index of six fish species: Sperata seenghala, Xenentodon cancila, Puntius sophore, Glossogobius giuris, Mastacembelus armatus and Eutropiichthys vacha, which belong to families Bagridae, Belonidae, Cyprinidae, Gobiidae, Mastacembelidae and Schilbeidae, respectively. Fish specimens were collected using a monofilament drift gill net, Current Jal (100-200 m long, 2 m depth, and mesh size 10-30 mm), and a trap net locally known as Khairel jal (8 m long, 10 m wide mouth, 1 m cod-end length and 5-10 mm cod-end mesh size). The estimated regression coefficient (b) of the length-weight relationship for these fish species ranged from 2.748 to 3.952, with an average of 3.188±0.43. Two species exhibited negative allometric growth (b<3), two species showed isometric growth (b=3) and the remaining two species exhibited positive allometric growth (b>3). The relative condition factor reveals that Puntius sophore is more robust than the other species. The hepatosomatic index value for the studied fish ranges from 0.79 to 3.03, with an average of 1.74±0.83. All the species’ liver weight positively correlates with body weight (r = 0.545-0.896). Keywords: Growth pattern, Hepatosomatic index, Indigenous fish, Relative condition factor, River Ganga